GOOD GOVERNANCE DAN PEMBARUAN HUKUM DI INDONESIA: REFLEKSI DALAM PENELITIAN SOSIO-LEGAL - Herlambang P Wiratraman (Jurnal Hukum dan Peradilan, 2013)
In the last decade post Soeharto, Good Governance (GG) has been often heard like a `mantra'. GG seems easily uttered talkative, formalized, and grew into a dominant political ideals as well as major constitutional and public administration discourse which have rooted in law, policy, and higher education. Like a rooster crowing in the morning, he continued to speak out in the mornings, wide box spawn 'governance, such as 'good forestry governance, 'good financial governance, 'good university governance, and many others. GG, in that context, seems like an appropriate nutrition to overcome the weakness of the Indonesian legal system, corrupt bureaucracy, and the predatoric political leadership. In this regard, it should be viewed more closely, what is actually superiority owned when GG is talked? Obviously, the law is one of the tools to ensure the operation of the mantra in its implementation, and based on master research conducted in 2005-2006, focusing on the issue of the Law Reform by applying a socio-legal approach. As a result, this study gave the fact which is different or even contrary to the ideals of political buildings or formalized or materialized law and policy. For example, one study showed that the GG in the context of legal reform in Indonesia actually very sinister and weakening the guarantee of human rights. Law, especially product of legislation and institutions, as well as its machinery transmission are dominant in advocating free market (free market friendly legal reform). Perhaps, the conclusions is not popular in the middle of the noisy speech spelling of GG and its projects. However, Indonesia today shows the continuation of massive corruption, violation of human rights, impunity and all the non protection situation in the Indonesian legal system.Keywords: Good Governance, Law reform, Sosio Legal approach